2022
DOI: 10.1177/08404704221139383
|View full text |Cite
|
Sign up to set email alerts
|

Health technology, quality and safety in a learning health system

Abstract: Health technology quality and safety is an important issue for health informatics (i.e. digital health) professionals. Health technologies have been used to (1) collect data that can be analyzed to improve the quality and safety of healthcare activities and (2) re-engineer and/or automate error-prone processes. Health technologies are also able to introduce new types of errors (i.e. technology-induced errors) and have been implicated in propagating errors across digital health ecosystems. To develop a learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Therefore, more focus on Health Technology Assessment guidelines specific to DHTs is needed. As the majority of assessment frameworks are based on solutions being CE-marked under the MDR, they could theoretically serve as a model for introducing health applications on prescription in other EU Member States ( 50 ). Once digital technologies are CE marked, joint HTAs similar to those already conducted in networks like the EUnetHTA could be an initial way of establishing benefit and provide a basis for reimbursement conditions to be specified in the countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, more focus on Health Technology Assessment guidelines specific to DHTs is needed. As the majority of assessment frameworks are based on solutions being CE-marked under the MDR, they could theoretically serve as a model for introducing health applications on prescription in other EU Member States ( 50 ). Once digital technologies are CE marked, joint HTAs similar to those already conducted in networks like the EUnetHTA could be an initial way of establishing benefit and provide a basis for reimbursement conditions to be specified in the countries.…”
Section: Discussionmentioning
confidence: 99%
“…As of current knowledge, there is evidence that digital improvements to existing technologies can reduce harm, but new technology and processes are always a risk factor for errors, as they increase burden on staff as the learning curve can be steep. A study looking at 10 years of health information technology failures found that incidents involving digital technologies are preventable in 75% of cases, with adequate staff training, and collaboration with clinicians during product development (48)(49)(50)(51). Every framework used to evaluate DHTs should contain patient safety aspect as first considerations.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from the incident analysis study [ 25 ] provided the foundation for the clinical informatics team and the embedded researcher to cocreate a new process that uses sociotechnical systems analysis for identifying, analyzing, and responding to HIT safety events. The new process used safety huddles [ 26 , 27 ] and was aligned with the concept of a learning health system in which theoretical frameworks and scientific evidence are integrated with internal data to inform continuous improvements [ 28 , 29 ]. Throughout the project, the researcher was positioned within the clinical informatics team with a constant focus on facilitating learning using adult learning principles [ 30 - 32 ], drawing on a variety of fields such as patient safety [ 17 , 18 , 20 , 33 , 34 ], quality improvement [ 35 - 37 ], and learning health systems [ 38 - 40 ] as well as HIT safety and harm specifically [ 5 , 41 - 45 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 5 7 Many scholars suggest that digital health is a way to improve both patient experience( 8 ) and clinical outcomes. 9 11 However, evidence remains limited regarding the role of digital health in advancing patient experience, with some research suggesting that digital health advances may not necessarily result in effectively meeting patient needs. 12 …”
Section: Introductionmentioning
confidence: 99%
“… 21 Currently, health systems continue to advance these digital health transformation efforts to strengthen system capacity to meet growing demands for care reduce cost and strengthen quality and safety performance. 4 , 10 , 11 However, the accelerated pace of digital transformation has now created an urgency to examine how digitally enabled care delivery impacts and influences patient experience, particularly given heightened complexity of care needs evident in the post pandemic era. 25 A growing number of digital tools in the consumer market offer patients a more flexible, and potentially cost-effective approach to managing health and care to meet consumer health needs.…”
Section: Introductionmentioning
confidence: 99%